THE EFFECTIVENESS OF FAMILY INTERVENTION MODEL ON PARENTS EFFECTIVE COMMUNICATION SKILLS IN SEXUAL VIOLENCE - Nur Kumala Dewi; Sri Nugroho Jati; Elly Trisnawati (State Islamic University (UIN) Ar-Raniry, 2023)
Sexual violence that occurs in children's classrooms places them with a significant impact on their health and lifelong well-being. This study aimed to identify the Family Intervention Model's effectiveness on parents' practical communication skills in preventing children from acts of sexual violence in border areas. This research comprised 23 wives and 23 husbands from Kecamatan Sajingan Besar. Qualitative data was collected with observations. During the research, the Parents Effective Communication Scale was used as means of quantitative data collection. The pre-test scale was given in the rapport-building session, and the post-test for the last session of intervention. The data has been analyzed using Wilcoxon Test. The Wilcoxon test showed the Z value is -5.437 with a significance value (p-value) of 0.000. The test significance value (p-value) is smaller than 0.05 (0.000 < 0.05), so there was a significant difference in parents' effective communication after the intervention.Keywords: effective communication; family intervention models; sexual violence